Recent Advances in Biofuel Cell and Emerging Hybrid System - Abdul Aziz Ahmad; Raihan Othman (Bandar Lampung University (UBL), 2013)
The present paper reviews the recent development of biofuel cell. Due to its renewable nature and milder operating conditions compared to conventional fuel cell, the electrochemical system has been extensively studied. However, major problems associated with this type of electrochemical system remain an intimidating challenge, the utmost being the low power output and stability of biocatalyst being used. Various attempts have been made to overcome these problems, some are reviewed here. The authors suggest a new direction in solving these problems by using hybrid system i.e. metal biofuel cell. The new hybrid system developed is of lower cost, less complex, higher OCV and greater power output.